Analisis Kesulitan Menulis Karangan Deskripsi di Kalangan Siswa Fase C Sekolah Dasar - Silviamagdalenabuulolo; Chandra Chandra; Inggria Kharisma (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze the difficulties faced by phase B learners in primary schools in the skill of writing description essays. The research method used is qualitative with a case study approach, which involves observation and in-depth interviews with 20 learners. The results of the analysis showed that the difficulties in writing description essays resulted from several factors, including a lack of understanding of text structure, a lack of vocabulary, and a lack of motivation to learn. In addition, environmental factors such as support from parents and teachers also affect students' writing ability. This research is expected to provide insights for teachers and related parties in improving description essay writing skills so that students can develop optimally.